A colorimetric and fluorometric probe for phenylhydrazine and its application in real samples. Issue 61 (11th July 2022) - Zhang, Zichang; Zhang, Dan; Qi, Qingrong; Li, Zicheng; Huang, Wencai
Abstract : An aromatic aldehyde-based fluorescent probe for phenylhydrazine detection was developed and its application in real water samples was demonstrated. Abstract : A fluorescent probe for phenylhydrazine detection was developed with aldehyde as the recognition group and good selectivity towards phenylhydrazine over hydrazine, hydroxylamine and other amines was observed. Its application in real water samples and fast visualization of phenylhydrazine using a probe-loaded paper strip were demonstrated.